Rationale, Procedures, and Response Rates for the 2015 Administration of NCI's Health Information National Trends Survey: HINTS-FDA 2015. Issue 12 (1st December 2016) - Blake, Kelly D.; Portnoy, David B.; Kaufman, Annette R.; Lin, Chung-Tung Jordan; Lo, Serena C.; Backlund, Eric; Cantor, David; Hicks, Lloyd; Lin, Amy; Caporaso, Andrew; Davis, Terisa; Moser, Richard P.; et al.
Abstract : The National Cancer Institute (NCI) developed the Health Information National Trends Survey (HINTS) to monitor population trends in cancer communication practices, information preferences, health risk behaviors, attitudes, and cancer knowledge. The U.S. Food and Drug Administration (FDA) recognized HINTS as a unique data resource for informing its health communication endeavors and partnered with NCI to field HINTS-FDA 2015. HINTS-FDA 2015 was a self-administered paper instrument sent by mail May 29 to September 8, 2015, using a random probability-based sample of U.S. postal addresses stratified by county-level smoking rates, with an oversampling of high and medium-high smoking strata to increase the yield of current smokers responding to the survey. The response rate for HINTS-FDA 2015 was 33% ( N  = 3, 738). The yield of current smokers ( n  = 495) was lower than expected, but the sampling strategy achieved the goal of obtaining more former smokers ( n  = 1, 132). Public-use HINTS-FDA 2015 data and supporting documentation have been available for download and secondary data analyses since June 2016 athttp://hints.cancer.gov . NCI and FDA encourage the use of HINTS-FDA for health communication research and practice related to tobacco-related communications, public knowledge, and behaviors as well as beliefs and actions related to medical products and dietary supplements.